Kisspeptin elicits cytosolic calcium responses through protein kinase C-dependent mechanism in immortalized RFamide-related peptide-3 neurons - Ozcan, Mete; Ozdemir, Gokcen; Kacar, Emine; Canpolat, Sinan; Kelestimur, Haluk (Wiley-Blackwell, 2015)
[Abstract Not Available]